Receiving as an attraction for perpetrators of theft crimes (decision study: Number 81/pid.B/PN.kbu) - Sanjaya, Diki; Fadhilah, Nisa (Journal of Law Science, 2025)
The phenomenon of shoplifting in Indonesia, which can occur in various conditions and based on its elements, and the importance of government strategies to reduce this problem. One of the issues raised was about receiving goods. Article 480 of the Criminal Code not only describes the legal challenges faced in upholding justice, but also illustrates the need to immediately address the socio-economic factors that drive individuals such as Mr. Gunadi Saputra to commit criminal acts, so that a comprehensive government strategy is needed including stricter law enforcement, which reflects the legal, social, and economic challenges faced by society. This study aims to analyze the application of Article 480 of the Criminal Code in the context of decision Number 81/Pid.B/2024/PN KBU, as well as the factors that make storing attractive for theft perpetrators. The method used is normative juridical, focusing on the analysis of laws and regulations and related literature. The results showed that the criminal acts committed by Mr. Gunadi Saputra as the backbone of the family were influenced by economic needs, a less supervising environment, and available opportunities. Therefore, a comprehensive approach is needed which includes strict law enforcement, public education, and improving economic welfare to create a safer and fairer environment for all.